Modern Linguistics: Bibliometric Analysis based on Scopus and Google Scholar (2019-2023) using VosViewer - Fitriani, Fitriani; Zuhriah, Zuhriah; Haeruddin, Haeruddin (Universitas Negeri Semarang, 2025)
The development of modern linguistics is spurred by technological advances and research methodologies, which encourage the utilization of new approaches such as corpus linguistics and bibliometric analysis. This method is essential for understanding the complexity of language in social and cultural contexts and identifying trends in research and scientific collaboration. This study aims to map the development of modern linguistics with a bibliometric approach using data from Scopus and Google Scholar from 2019 to 2023. The main objective of this study is to identify patterns of publications, scientific collaborations, and thematic clusters in linguistics. The methods used include bibliometric analysis with VOSviewer software to visualize the data. The analysis results reveal four main clusters in the Scopus data: traditional linguistics, computational linguistics, applied linguistics, and corpus linguistics. Meanwhile, an analysis from Google Scholar shows five clusters that show significant contributions from developing countries, especially in Southeast Asia. The United States and Western European countries were identified as the dominant centers of scientific collaboration, while the involvement of developing countries was limited. These findings highlight the integration between linguistics and technology and a shift in research focus towards interdisciplinarity. This research provides important insights for understanding the modern linguistic scientific landscape. It offers strategic implications for researchers, journal editors, and policymakers in designing research directions more responsive to global challenges.